The Use of Android Game to Improve Impaired Hearing Students Vocabulary Mastery - Putri, Indah Cantika; Damri, Damri; Engkizar, Engkizar; Asril, Zainal; Efendi, Efendi (Department of Special Education, 2022)
This study aims to analyze the use of android game to improve impaired hearing students vocabulary mastery at one of Special Schools in Padang City, Indonesia. This study used quantitative research method with Single Subject Research (SRR) approach, the research data was taken from one impaired hearing student through seventeen direct lessons using android game. All the data that the authors obtained were analyzed descriptively using visual graph analysis tools, this method of analysis is one of the techniques for analyzing Single Subject Research. The results of the study showed that the use of Android game as a learning media significantly improved the impaired hearing student vocabulary mastery. This increase in ability is proved by the initial test scores of the participants at a score of 10, 10, 20, 20, 20, this score is the score before learning by using android game. Furthermore, after the author did seven times direct treatment, it was found that the students’ scores increased to 40, 50, 70, 80, 70, 70, 70, even students were able to obtain final self-evaluation scores with a score of 50, 70, 100, 100, 100. The results of this study proved that the use of android gamehas succeeded in increasing the vocabulary mastery of impaired hearing students